RISK FACTOR ANALYSIS OF HYPERTENSION DISEASE IN THE ELDERLY AT GIRIREJO STASI IN SAMARINDA - Pertiwi, Gracia Herni; Sastrini, Yovita (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The aims of the study were to determine: (1) the relationship between family history and the incidence of hypertension (2) the relationship between physical activity and the incidence of hypertension; (3) the relationship between cholesterol and the incidence of hypertension, and (4) the relationship between body mass index and the incidence of hypertension in the elderly.The research was conducted from March – May 2022 at Girirejo Stasi, Samarinda City. The research design used was analytic survey research or analytical observational (non-experimental) with a cross-sectional approach.The population of this study were all elderly people living in the city of Samarinda. A total sample of 30 elderly people was selected based on inclusion and exclusion criteria.Data was collected using a questionnaire, filling out each question item directly to the respondent, consisting of: age, gender and type of work, activity level, cholesterol level, blood pressure, body mass index, family history of hypertension.The results showed that: (1) There was a relationship between a family history of disease and the incidence of hypertension; (2) There is a relationship between physical activity and the incidence of hypertension in the elderly; (3) there is no relationship between body mass index and the incidence of hypertension, and (4) there is a relationship between cholesterol levels and the incidence of hypertension.